2020
DOI: 10.1128/aac.01025-20
|View full text |Cite
|
Sign up to set email alerts
|

Achromobacter Infections and Treatment Options

Abstract: Achromobacter is a genus of non-fermenting Gram negative bacteria under order Burkholderiales. Although primarily isolated from respiratory tract of people with cystic fibrosis, Achromobacter spp. can cause a broad range of infections in hosts with other underlying conditions. Their rare occurrence and ever-changing taxonomy hinder defining their clinical features, risk factors for acquisition and adverse outcomes, and optimal treatment. Achromobacter spp. are intrinsically resistant to several antibiotics (e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
125
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(130 citation statements)
references
References 99 publications
(98 reference statements)
1
125
2
2
Order By: Relevance
“…Otherwise, therapy should be guided by antimicrobial susceptibility testing results. For Axc , the most active agents beside co-trimoxazole are minocycline, meropenem, or imipenem, piperacillin-tazobactam, ceftazidime, and/or chloramphenicol, depending on the study [ 150 , 151 , 152 , 153 ]. For Sm , chloramphenicol, minocycline, or doxycycline can be considered for the treatment, as well as ticarcillin-clavulanate, ceftazidime, and levofloxacin, for which clinical breakpoints are available.…”
Section: Pathoadaptive Traitsmentioning
confidence: 99%
“…Otherwise, therapy should be guided by antimicrobial susceptibility testing results. For Axc , the most active agents beside co-trimoxazole are minocycline, meropenem, or imipenem, piperacillin-tazobactam, ceftazidime, and/or chloramphenicol, depending on the study [ 150 , 151 , 152 , 153 ]. For Sm , chloramphenicol, minocycline, or doxycycline can be considered for the treatment, as well as ticarcillin-clavulanate, ceftazidime, and levofloxacin, for which clinical breakpoints are available.…”
Section: Pathoadaptive Traitsmentioning
confidence: 99%
“…The substrates and the family of the other six pumps have yet to be determined. A comparative genomic analysis showed that the genes coding for most of these nine systems are conserved among different A. xylosoxidans strains [34], with one of them, axyABM, conserved in all the sequenced Achromobacter genomes [36], while axyXY-oprZ has been found also in Achromobacter ruhlandii [37]. Regarding proteins belonging to the HME family, RND transport systems homologous of CzcABC and CusABC are present in the genomes of other Achromobacter strains [38,39].…”
Section: Rnd Efflux Pump Families In Cf Pathogensmentioning
confidence: 99%
“…These bacteria can cause bacteraemia, meningitis and urinary tract infections [ 323 , 324 , 325 ]. Moreover, Achromobacter genus-belonging bacteria have also been isolated from CF patients [ 326 , 327 , 328 ]. Achromobacter xylosoxidans is the predominantly reported species among CF clinical isolates [ 322 ], but other Achromobacter species have also been isolated from these patients, such as Achromobacter ruhlandiiand [ 329 ].…”
Section: Emerging Opportunistic Pathogens With Environmental Originmentioning
confidence: 99%
“…Achromobacter xylosoxidans is the predominantly reported species among CF clinical isolates [ 322 ], but other Achromobacter species have also been isolated from these patients, such as Achromobacter ruhlandiiand [ 329 ]. They are intrinsically resistant to several drugs [ 328 ] due to the presence in their genomes of genes encoding RND MDR efflux pumps that extrude cephalosporins, aztreonam, carbapenems, quinolones, chloramphenicol, tetracyclines and erythromycin [ 330 , 331 ], as well as to the activity of β-lactamases [ 332 , 333 ]. Moreover, they are becoming increasingly resistant to carbapenems [ 328 ].…”
Section: Emerging Opportunistic Pathogens With Environmental Originmentioning
confidence: 99%
See 1 more Smart Citation